Pengaruh Manajemen Afirmasi Terhadap Tingkat Stress Pada Pasien Chronic Kidney Disease Yang Menjalani Haemodialisa - Susanti, Desi; Fuspita, Hetty; Eliyanti, Yeni; Amita, Dita; Yatimah, Yatimah (Universitas Malahayati, 2023)
ABSTRACT Patients who have been diagnosed with end-stage kidney disease have a frequency of 2-3 times undergoing hemodialysis therapy. They spend several hours each week on therapy, these conditions make them experience tension, anxiety, stress and depression which vary at the level of stress for each individual which can lead to physiological and psychological changes that will have a negative impact on their quality of life and health. One way to reduce stress is to do positive affirmations. Purpose: The aim of the study was to determine the effect of affirmative management on stress levels in Chronic Kidney Disease patients undergoing hemodialysis at Harapan and Doa Hospital, Bengkulu City. In this study used a quasi-experimental research method with pre-test and post-test approaches. The sampling technique was purposive sampling of 10 samples. The research was conducted on May 30 – June 30 2021. Data were analyzed univariately and bivariately using the paired sample t test statistical test. The results of the study obtained a p value of 0.000 (p <0.05) with an average value of stress level before the affirmative action was 34.10 and the average after the affirmation was 25.0. There is an effect of affirmative management on stress levels in Chronic Kidney Disease patients undergoing hemodialysis at the hospital. Hope and Prayer of Bengkulu City. Suggestions for affirmative research are good for people with CKD to reduce stress levels. Keywords: chronic kidney disease, affirmation, stress level ABSTRAK Pasien yang telah didiagnosa menderita penyakit ginjal tahap akhir berada pada frekuensi 2-3 kali menjalani terapi hemodialisa. Mereka setiap minggunya menghabiskan waktu beberapa jam untuk terapi, kondisi tersebut membuat mereka mengalami ketegangan, kecemasan, stres serta depresi yang berbeda-beda pada tingkatannya pada stres setiap individu dapat mengakibatkan perubahan secara fisiologi maupun secara psikologi yang akan berdampak negatif terhadap kualitas hidup dan kesehatannya.Salah satu cara mengurangi stress adalah dengan dilakukan afirmasi yang bersifat positif. Tujuan penelitian untuk mengetahui pengaruh pemberian manajemen afirmasi terhadap tingkat stress pada pasien Chronic Kidney Disease yang menjalani haemodialisa di RS.Harapan dan Doa Kota Bengkulu. Metode penelitian secara quasi experimen dengan metode pendekatan pre test dan post test. Teknik pengambilan sampel purposive sampling sebanyak 10 sampel. Penelitian dilaksanakan pada tanggal 30 Mei – 30 Juni 2021. Data dianalisis secara univariat dan bivariat dengan uji statistic paired sampel t test. Hasil penelitian didapatkan p value 0,000 (p < 0,05) dengan nilai rerata tingkat stress sebelum tindakan afirmasi 34,10 dan rerata setelah dilakukan afirmasi 25,0. Simpulan terdapat pengaruh pemberian manajemen afirmasi terhadap tingkat stress pada pasien Chronic Kidney Disease yang menjalani haemodialisa di RS. Harapan dan Doa Kota Bengkulu. Saran penelitian afirmasi baik dilakukan pada penderita CKD untuk menggurangi tingkat stress Kata Kunci: Chronic Kidney Disease, Afirmasi, Tingkat Stress